DAMPAK AKSES AIR MINUM DAN SANITASI TERHADAP PENINGKATAN - Kustanto, Deka Nata (Jurnal Sosial Ekonomi Pekerjaan Umum, 2015)
Access to drinking water and safe sanitation are important in determining life expectancy. Construction of water and sanitation affect on health status, because the water and sanitation infrastructure is part of factors builder life expectancy. With increasing access to water and proper sanitation at the individual, household and society, will degrade society diseases and contribute to the increase in life expectancy resulting in an increase in the welfare of society. Using data from countries and cities in Indonesia in 1999 to 2013 to see the changes in life expectancy . We focused look at the role of water and sanitation because according to available data, there is a significant increase in household access to drinking water and improvement of sanitation. This variable will be used in explaining the variation in life expectancy changes. This paper will contribute to the development of health by looking at the factors that determine the increase in life expectancy in developing countries.